Contaminant concentrations and biomarkers in 21-day old Herring Gulls (Larus argentatus) and Double-crested Cormorants (Phalacrocorax auritus) from eastern Lake Ontario, and from Hamilton Harbour in western Lake Ontario in 1989 and 1990. Issue 2 (2nd April 2016) - Bishop, Christine A.; Trudeau, Suzanne; Janz, David; Hughes, Kimberley D.
Abstract : This study measured concentrations of polychlorinated biphenyls, polycyclic aromatic hydrocarbons, organochlorine pesticides, trace metals and biochemical markers of contaminant exposure and potential toxicity (plasma and hepatic retinol, hepatic retinyl palmitate, ethoxyresorufin O-deethylase, hepatic porphyrins) in 21 day-old Herring Gull ( Larus argentatus ) and Double-crested Cormorant ( Phalacrocorax auritus ) chicks. The chicks were collected from breeding colonies at Hamilton Harbour, an industrialized site in western Lake Ontario, and at Snake and Pigeon Islands in eastern Lake Ontario in 1989 and 1990. The polycyclic aromatic hydrocarbons, benzo[a]pyrene and naphthalene, were detected in bile and concentrations were higher in both species, but particularly in Cormorants, at Hamilton Harbour in comparison to eastern Lake Ontario. Ethoxyresorufin O-deethylase activity correlated positively with polyaromatic hydrocarbon exposure in Cormorants. At Hamilton Harbour, Cormorants had significantly greater liver to body weight ratios, increased hepatic ethoxyresorufin O-deethylase activities and elevated plasma retinol concentrations compared to those from eastern Lake Ontario. Liver concentrations of selected polychlorinated biphenyl congeners were generally low (<2 ug g −1 w.wt) in birds from both areas but Hamilton Harbour Herring Gulls had mean concentrations that were significantly higher than eastern Lake Ontario Gulls, while Cormorants had low and similar polychlorinated biphenyl concentrations between sites. Trace metal levels did not vary substantially between sites for either species.